2016
DOI: 10.17219/acem/62347
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Two Approaches to Laparoscopic Adrenalectomy: Lateral Transperitoneal Versus Posterior Retroperitoneal Approach

Abstract: diovascular and respiratory diseases, or those with obesity [1]. However, novel methods may prolong operative time when employed by trainee surgeons.During surgical procedures, the proper exposure of paired adrenal glands is challenging due to their small size, fragility and localization in the retroperitoneal area (deep inside the adipose tissue). Classical interventions require extensive incisions through integuments that are disproportionately large compared to the size of the glands [3].Surgery has recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Adrenal tumors which need surgical intervention are broadly classified into functional or nonfuctional. In our study, supported by other studies ( 1 , 5 , 7 - 9 ) , the majority of operated tumors were non-functional. Younger patients were found to be more likely to have functional tumors, but in contrary to what reported by Wooten and King ( 10 ), we found that males were more likely than females to have functional adrenal tumors.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Adrenal tumors which need surgical intervention are broadly classified into functional or nonfuctional. In our study, supported by other studies ( 1 , 5 , 7 - 9 ) , the majority of operated tumors were non-functional. Younger patients were found to be more likely to have functional tumors, but in contrary to what reported by Wooten and King ( 10 ), we found that males were more likely than females to have functional adrenal tumors.…”
Section: Discussionsupporting
confidence: 90%
“…Propper exposure requires extensive incisions much larger than their size. Because of this, LA represented an attractive alternative to open approach since first report of LA in 1992 ( 3 , 5 , 6 ). Adrenal tumors which need surgical intervention are broadly classified into functional or nonfuctional.…”
Section: Discussionmentioning
confidence: 99%
“…Of 592 retrieved studies, 573 articles were excluded for different reasons.Finally, 19 studies [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] were included in our analysis. Table 1 lists the basic characteristics of the included studies in the meta-analysis,and Table 2 shows the clinical and pathologic characteristics of the included studies.The two groups were similar in age (MD -4.03, 95% CI -8.82 to 0.76, P = 0.10), BMI (MD 0.17, 95% CI -0.53 to 0.87, P = 0.64), proportion of right sided (OR 0.91, 95% CI 0.74 to 1.12, P = 0.35), proportion of bilateral lesions (OR 1.21, 95% CI 0.52 to 2.80, P = 0.65),and previous abdominal surgery (OR 0.91, 95% CI 0.59 to 1.43, P = 0.70),as shown in Fig.4A-E.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Nevertheless, PRA requires much higher pressure of CO 2 insufflation as compared to LTA (25 vs. 12 mm Hg). As a consequence, renal veins and inferior vena cava during right-sided PRA are compressed for as long as 30-150 minutes, depending on the difficulty of the operation and the surgeon's experience [13][14][15]. In some patients after adrenalectomy Ass.…”
Section: Introductionmentioning
confidence: 99%